2012
DOI: 10.1007/s10773-012-1088-8
|View full text |Cite
|
Sign up to set email alerts
|

Thick Domain Walls Coupled with Viscous Fluid and Electromagnetic Field in Lyra Geometry

Abstract: In this paper, we have obtained plane symmetric cosmological models of thick domain walls with viscous field coupled with electromagnetic field in the framework of Lyra geometry, by using equation of state. Physical and geometrical implications of the models are also discussed in the presence of magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Eqs. (38) and (39) show that this model of ̃ gravity is not free from shear scalar, and the model's behavior is totally anisotropic provided .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eqs. (38) and (39) show that this model of ̃ gravity is not free from shear scalar, and the model's behavior is totally anisotropic provided .…”
Section: Discussionmentioning
confidence: 99%
“…The magnetic field [35][36][37] found in both galactic and intergalactic space has played a significant role in understanding the distribution of energy in the Universe. Numerous authors have explored the influence of magnetic fields on cosmological development in diverse circumstances, both theoretically and practically [38][39][40][41][42][43][44][45][46]; Melvin [47] has also revealed that matter was strongly ionized and seamlessly associated with the field during the development of the Universe.…”
Section: Introductionmentioning
confidence: 99%